Gender Differences In Writing Styles In Magazine Articles - Siaw, Jacqueline Chin Chin (Universiti Malaysia Sarawak (UNIMAS), 2017)
This study investigates the gender differences in writing styles in magazine articles. It examines the types of hooks and endings used by male and female writers, the types of punctuation marks used, as well as their usage. A total of I 9 articles ( 6 males, 13 females) from Kuching In and Out's (KJNO) "I Love Kuching " column were used. The findings of the study indicate that there are gender differences, particularly in the hooks and endings used, and certain types of punctuation. In hook writing, new strategies, such as flashbacks and selfintroduction were found, in which only the male writers used the self-introduction strategy. They also used only one strategy to write their hooks, whereas female writers combined more than one strategy. As for endings, it was the opposite, in which male writers combined more than one strategy and female writers only used one strategy. Furthermore, greetings and statement of future plans were among the new strategies found for ending writing, in which only the female writers used greetings to end their articles. As for punctuation marks used, there were a total of 13 punctuation marks found. Certain punctuations such as capitalisation and quotation marks showed differences in their usages such as the use of capitalised expression words and quotes only among female writers. There were contradictions, as well between the findings with previous studies in the usage of question marks and slashes, as the findings in this study indicate that male writers used more question marks and slashes. Overall, it was concluded that female writers were more expressive and had more variation in their writing based on the way they write their hooks, endings, and usage of punctuation marks.